PENERAPAN KAIZEN PADA LINE TRIMMING UNTUK MENINGKATKAN JUMLAH PRODUKSI KACA PENGAMAN - Teguh Sri Ngadono (Universitas Mercu Buana, 2018)
PT. XYZ is automotive component manufacture that produce safety glass are tempered safety glass and laminate safety glass that are supplied to the car maker manufacture in domestic and overseas. Safety glass that are produced by PT. XYZ is for OEM (Original Equipment Manfacture) and ARG (Automotive Replacement Glass). Due to demand from customer always increase in every year, so many things that should be done for improvement on production line to increase production quantity resulted beside additional new production machine. The objective of this research is to improve the laminate production department on the trimming line where on this process is the latest production process that will determine finish good result. There is improvement that was done on this trimming production line is on the loading glass method that firstly is done manually by operator then changed by use supporting tools that is called felting. After kaizen is done, the production result that previously is 1,588 glasses per shift increase to be 1,791 glasses per shift or increase 12.8%. By this increasing production result is hoped the production plan on the next year and there is buffer stock if any additional demand suddenly. This kaizen implementation is suggested can be implemented in others process line that the loading glass method is still manually.